Stacked spherical calcium carbonate and preparation method thereof

By using the response of limestone and sodium carbonate solution during calcium carbonate preparation, combined with crystal control agents, stacking spherical calcium carbonate was successfully prepared, solving the problem of lack of this shape preparation method in the existing technology, and achieved efficient and economical economy The preparation of calcium carbonate materials has expanded its application field.

CN119330390APending Publication Date: 2025-01-21GUANGXI HUANA NEW MATERIALS TECH CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202411622528.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-14
Publication Date
2025-01-21

AI Technical Summary

Technical Problem

The lack of effective methods for the preparation of stacked spherical calcium carbonate in the prior art limits its application potential in various fields.

Method used

By calcining limestone to prepare lime and reacting with sodium carbonate solution under specific conditions, combined with the use of a crystal form control agent, the preparation of stacked spherical calcium carbonate is achieved.

Benefits of technology

Successfully prepared stacked spherical calcium carbonate with high purity, good dispersion and excellent mechanical strength, broadening its application potential in rubber, plastics, coatings, papermaking, medicine and other fields.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119330390A_ABST
    Figure CN119330390A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method of stacked spherical calcium carbonate, which comprises the following steps: S1, calcining limestone to prepare lime, digesting the lime, standing, sieving and removing impurities to obtain lime slurry; s2, metering the amount of sodium carbonate according to a chemical equation, and preparing a sodium carbonate solution for later use; s3, weighing water, pouring the water into a carbonization tower, controlling the initial water temperature, adding a crystal form control agent, and starting stirring; s4, dropwise adding lime slurry and a sodium carbonate solution into the carbonization tower by using a pump for reaction, and after dropwise adding is completed, continuously stirring for full reaction; s5, heating the reacted solution, and carrying out heat preservation and aging; and S6, carrying out suction filtration, drying and sieving on the suspension obtained in the step S5 to finally obtain the stacked spherical calcium carbonate. The stacked spherical calcium carbonate is prepared by using the lime slurry and the sodium carbonate as main raw materials, the raw materials are easy to obtain, the cost is low, the operation process is simple, the dispersity is good, a new way is provided for research and development of the morphology of the calcium carbonate, and the method has a good application prospect.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the technical field of calcium carbonate, and in particular relates to stacked spherical calcium carbonate and a preparation method thereof. Technical Background

[0002] Calcium carbonate is an important inorganic compound, usually white crystals. Due to its advantages of non-toxicity, high whiteness, non-irritation, low price, good color, etc., it is widely used in many fields such as papermaking, plastics, inks, medicine, cosmetics, food, coatings, etc. It has been used for more than 100 years. The morphology, particle size and surface modification of calcium carbonate have a huge impact on the filling effect, among which morphology is an extremely critical factor. Precipitated calcium carbonate with different morphologies has different application performance and fields.

[0003] Spindle-shaped calcium carbonate is low in price and can significantly improve the whiteness of materials when used in plastics, but the strength of the resulting plastic products is not high; rod-shaped calcium carbonate has good strength, impact resistance and processing fluidity when used in plastic products, but rod-shaped calcium carbonate is in the aragonite phase and has poor storage stability; spherical nano calcium carbonate has a simple structure, small stacking volume, good smoothness, fluidity, and high hiding power, and is mainly used in papermaking, lubricating oil, and electronic ceramics; chain-shaped nano calcium carbonate is a reinforcing filler that can significantly improve the strength, elongation, hardness, and wear resistance of materials, and is widely used in the rubber field; cubic nano calcium carbonate is the largest amount of nano calcium carbonate used in industry, and is often used in sealants and paper, showing high shading, flatness, and whiteness; flaky calcium carbonate has a strong surface hiding power and has good optical and printing properties; therefore, the preparation of precipitated calcium carbonate products with different morphologies to improve their application performance and added value is still a hot topic in the industry and an important direction of modern inorganic material science research.

[0004] Patent CN109809458A provides a rugby-shaped calcium carbonate and its preparation process, which adds heated and cooked soluble starch slurry, polyvinyl pyrrolidone, sodium polyvinyl benzene sulfonate, polyethylene imine, one or more of them as crystal directing agents to calcium hydroxide slurry, adjusts the carbonization temperature, and then introduces CO2 to carbonize until the pH is lower than 8 to obtain rugby-shaped calcium carbonate. The rugby-shaped calcium carbonate prepared by this method has a controllable particle size within the range of 300 to 900 nanometers, has good processing fluidity as a downstream product filler, and has a high added value as a template material for hollow particles, and is suitable for the food, medicine, and cosmetics industries.

[0005] Patent CN106118135B provides a method for preparing a hemispherical calcium carbonate structure, wherein one or more of calcium fluoride, calcium chloride and calcium nitrate are dissolved in water to prepare a solution, dextrin is added after adjusting the pH to 4-5, a quaternary ammonium salt cationic surfactant is added after stirring at 50-70°C, a flowing mixed gas of NH3 and CO2 is introduced to react for 4-24 hours, and hemispherical calcium carbonate is obtained by filtering, washing with alcohol and spray drying. The calcium carbonate filler of the invention improves the affinity to organic polymers and improves the acid resistance and smoothness of the filler.

[0006] Patent CN104445334A provides a method for preparing sheet-stacked cubic micron-sized calcium carbonate. Using inorganic material graphene sheets as templates, soluble calcium salts and soluble carbonates are reacted to synthesize micron-sized calcium carbonate particles at room temperature. The prepared calcium carbonate particles have uniform particle size distribution and good monodispersity.

[0007] Patent CN114455620B provides a method for preparing square and cluster-shaped micron-sized calcium carbonate, which is prepared into a CaCl2 reverse microemulsion and a Na2CO3 reverse microemulsion; the Na2CO3 reverse microemulsion is added to the CaCl2 reverse microemulsion, and after the addition is completed, the micron-sized calcium carbonate with square and cluster-shaped symbiosis is obtained by aging. The calcium carbonate obtained by the invention has good anti-powdering and anti-settling properties as a filler in paper, coatings, paints and plastics.

[0008] Patent CN112591780A provides a method for preparing woven calcium carbonate. The invention uses calcium chloride and ammonium carbonate as raw materials, 1-naphthoic acid as an inducer, and adopts a gas diffusion method to realize the formation and preparation of woven calcium carbonate at the interface of an organic phase and an aqueous phase.

[0009] Patent CN108439447A provides a method for preparing calcium carbonate with a layered structure. In a carbon dioxide atmosphere, in a mixed solution of flexible polymer nanowires and calcium chloride, calcium carbonate crystals form a layered structure. The layered calcium carbonate structure prepared by this method is very close to the structure of shellfish in nature, with a single and regular crystal form and a simple preparation process, providing an efficient method for artificial preparation of calcium carbonate.

[0010] Patent CN112408448A provides a method for preparing mulberry-shaped calcite micron calcium carbonate; Patent CN116040671A provides a method for preparing flaky calcium carbonate; Patent CN111592026A provides a method for preparing discus-shaped micron calcium carbonate.

[0011] The above patents prepare calcium carbonate of different morphologies by different methods, which contributes to the diversity of calcium carbonate morphology and expands the application field and performance of calcium carbonate. However, there are few reports on the method for preparing stacked spherical calcium carbonate in the existing patents. The present invention is different from the existing technology and provides a method for preparing stacked spherical calcium carbonate. Summary of the invention

[0012] The object of the present invention is to provide a method for preparing stacked spherical calcium carbonate. The following technical scheme is adopted:

[0013] A method for preparing stacked spherical calcium carbonate comprises the following steps:

[0014] S1: calcining limestone to prepare lime, and preparing lime slurry by digesting, standing, and sieving to remove impurities;

[0015] S2: according to the chemical reaction equation, the amount of sodium carbonate is measured and the sodium carbonate solution is prepared for standby use;

[0016] S3: Pour weighed water into the carbonization tower, control the initial water temperature, add a crystal form control agent, and start stirring;

[0017] S4: using a peristaltic pump to simultaneously add lime slurry and sodium carbonate solution to the carbonization tower at a certain drop rate for reaction. After the dropwise addition is completed, continue stirring to fully react;

[0018] S5: heating the reacted solution, and then keeping the temperature for aging;

[0019] S6: The suspension obtained in step S5 is filtered, dried and sieved to finally obtain stacked spherical calcium carbonate.

[0020] Furthermore, in step S1, limestone is calcined at 1000° C. for 300 min to prepare lime; the standing time is 48 h; and the solid content of the lime slurry is adjusted to 7-11% for standby use.

[0021] Furthermore, the sodium carbonate solution in step S2 is prepared at a concentration of 0.1 to 0.5 mol / L.

[0022] Furthermore, in step S3, 10 kg of tap water is weighed and poured into the carbonization tower, and the initial water temperature is controlled to be 35-50° C.; the crystal form control agent is compounded by N-hydroxyethylethylenediaminetriacetic acid and ammonium sulfate in a mass ratio of 1:1, and the added amount is 0.3-1.5% of the dry basis mass of the lime slurry.

[0023] Furthermore, the stirring speed in step S3 is 600 r / min.

[0024] Furthermore, in step S4, the lime slurry dropping rate is 50-100 mL / min, and the sodium carbonate solution dropping time is consistent with the lime slurry dropping time.

[0025] Furthermore, in step S4, stirring is continued for 0.5 h.

[0026] Furthermore, in step S5, the insulation temperature is 90° C. and the insulation aging is performed for 1 to 3 hours.

[0027] Furthermore, the drying process temperature in step S6 is 100° C., and the product is dried in an oven.

[0028] Technical principle of the present invention:

[0029] When discussing the preparation method of stacked spherical calcium carbonate in depth, we should not only elaborate on the specific operation and details of each step, but also analyze the role of each raw material, the synergy between them, and how to significantly improve the physical and chemical properties of the product by precisely controlling these factors, thereby showing the significant technical progress of the present invention, which is specifically manifested in the following aspects:

[0030] 1. Specific role and synergistic effect of raw materials

[0031] (1) Conversion of limestone and lime: Limestone is used as the starting material and calcined at 1000°C for 300 minutes. This high temperature treatment not only effectively decomposes the calcium carbonate in the limestone to generate highly active calcium oxide (lime), but also removes impurities in the raw materials through long-term high temperature, providing a pure reaction basis for subsequent reactions. The lime is digested and left to stand for 48 hours to ensure full hydration, forming a fine and stable lime slurry with a solid content of 7-11%. This range not only ensures the uniformity of the reaction, but also avoids the agglomeration problem caused by excessive concentration.

[0032] (2) Preparation of sodium carbonate solution: Sodium carbonate solution with a concentration of 0.1-0.5 mol / L is prepared. This concentration range is carefully calculated to react with calcium hydroxide in the lime slurry in the best proportion to form calcium carbonate precipitation. As a precipitant, the precise control of the concentration of sodium carbonate directly affects the particle size distribution and morphology of the product.

[0033] (3) The role of the crystal form control agent: The crystal form control agent is a compound of N-hydroxyethylethylenediaminetriacetic acid and ammonium sulfate in a mass ratio of 1:1, and its addition amount is 0.3-1.5% of the dry weight of the lime slurry. This compounding agent plays a role in "fine-tuning" the crystal growth during the reaction process. By adsorbing on the crystal surface, it changes the charge distribution and energy state of the crystal surface, thereby guiding the calcium carbonate molecules to arrange in a specific direction to form a stacked spherical structure.

[0034] (4) Initial water temperature and stirring: 10 kg of tap water was used as the reaction medium, and the initial water temperature was controlled at 35-50 °C. This temperature range helps to promote the reaction rate while avoiding side reactions caused by excessively high temperatures. The stirring speed was set at 600 r / min to ensure that the reactants were evenly mixed in the carbonization tower, which promoted the sufficiency and uniformity of the reaction.

[0035] 2. The importance of raw material dosage control

[0036] Accurately controlling the amount of each raw material is the key to preparing high-quality stacked spherical calcium carbonate. Excessive or insufficient sodium carbonate will directly affect the purity and form of the product; the adjustment of the solid content of the lime slurry is related to the reaction speed and the fineness of the final product; the amount of crystal form controller added directly determines the crystal structure and performance of the product. Therefore, the amount of each step must be strictly calculated and experimentally verified to ensure the best technical effect.

[0037] 3. Non-interchangeability of preparation steps and optimization of process parameters

[0038] The preparation steps of the present invention are closely linked and cannot be arbitrarily replaced. For example, if sodium carbonate solution is added first and then lime slurry is added dropwise, it will cause rapid reaction and be difficult to control, and it is impossible to form an ideal stacked spherical structure. Similarly, the time and temperature of the heat preservation and aging stage are also carefully designed. Too short a time or too low a temperature cannot make the crystal fully grow and stabilize, and too long a time or too high a temperature may cause unnecessary phase change or structural damage. By screening and optimizing these process parameters, the present invention has achieved unexpected technical effects, that is, successfully preparing stacked spherical calcium carbonate with high purity, good dispersibility and excellent mechanical strength, which is of great significance in materials science and industrial applications.

[0039] Compared with the existing calcium carbonate preparation technology, the present invention has many significant technical advantages, which not only profoundly innovates the traditional production process, but also opens a new chapter in the development of the calcium carbonate material field, which is specifically manifested in the following aspects:

[0040] (1) In terms of raw material selection, the present invention takes a unique approach and uses lime slurry and sodium carbonate as core raw materials. Both raw materials are abundant and easy to obtain in nature, which not only reduces the difficulty of obtaining raw materials, but also greatly reduces production costs, making the entire production process more economical and environmentally friendly. By accurately controlling the initial water temperature, the present invention cleverly utilizes the effect of temperature on chemical reaction rate and product morphology, ensures the stability and controllability of the reaction process, and lays a solid foundation for the subsequent generation of high-quality calcium carbonate products.

[0041] (2) The present invention innovatively introduces the key element of crystal form controller. This measure breaks the limitation of single morphology of calcium carbonate in traditional preparation process. By precisely controlling the type and amount of crystal form controller, the orderly arrangement of calcium carbonate crystals during the growth process is successfully guided, and finally a calcium carbonate product with a unique stacked spherical structure is obtained. This special morphology not only gives calcium carbonate more excellent physical and chemical properties, such as higher specific surface area and stronger adsorption capacity, but also provides unlimited possibilities for its application in multiple fields.

[0042] (3) From the perspective of the operating process, the present invention also shows great superiority. The entire preparation process is reasonably designed, the steps are clear, the operation is simple and easy, and large-scale industrial production can be achieved without complex equipment and strict operating conditions. This not only reduces the production difficulty and cost, but also improves the production efficiency and the stability of product quality, bringing significant economic and social benefits to the enterprise.

[0043] (4) The stacked spherical calcium carbonate product of the present invention also shows good application prospects. Its unique morphology and excellent performance make it have wide application potential in many fields such as rubber, plastics, coatings, papermaking, and medicine. For example, in the rubber industry, it can be used as a reinforcing agent to improve the strength and wear resistance of rubber products; in the coating industry, it can be used as a filler to enhance the hiding power and stability of the coating. Therefore, the successful development of the present invention not only provides new ideas and methods for the research and development of calcium carbonate morphology, but also injects new vitality and motivation into the development of related industries.

[0044] In summary, compared with the prior art, the present invention has achieved significant progress in raw material selection, process design, product morphology and performance improvement, opening up a new path for the preparation and application of calcium carbonate materials, and has broad market prospects and far-reaching social significance. BRIEF DESCRIPTION OF THE DRAWINGS

[0045] Figure 1 This is an electron microscope photo of the product of Example 1;

[0046] Figure 2 This is an electron microscope photo of the product of Example 2;

[0047] Figure 3 This is an electron microscope photo of the product of Example 3;

[0048] Figure 4 This is an electron microscope photo of the product of Comparative Example 1;

[0049] Figure 5 This is an electron microscope photo of the product of Comparative Example 2;

[0050] Figure 6 This is an electron microscope photo of the product of Comparative Example 3. DETAILED DESCRIPTION

[0051] The following examples are given to illustrate the present invention in more detail. It should be emphasized that the following description is only exemplary and is not intended to limit the scope of the present invention and its application.

[0052] Example 1

[0053] A method for preparing stacked spherical calcium carbonate comprises the following steps:

[0054] S1: limestone is calcined at 1000°C for 300 min to prepare lime, the lime is digested, left to stand for 48 hours, and sieved to remove impurities to prepare lime slurry, and the solid content of the lime slurry is adjusted to 9% for standby use.

[0055] S2: Measure the amount of sodium carbonate according to the chemical reaction equation and prepare a sodium carbonate solution for use.

[0056] S3: Weigh 10 kg of tap water and pour it into the carbonization tower, control the initial water temperature to 48°C, add a crystal control agent, and start stirring.

[0057] S4: Use a peristaltic pump to simultaneously add lime slurry and sodium carbonate solution to the carbonization tower at a certain drop rate for reaction. After the drop addition is completed, continue stirring for 0.5h to allow sufficient reaction.

[0058] S5: The reacted solution was heated to 90°C and kept warm for 2 hours.

[0059] S6: The suspension obtained in step S5 is filtered, dried and sieved to finally obtain stacked spherical calcium carbonate.

[0060] The sodium carbonate solution is prepared at a concentration of 0.3 mol / L.

[0061] The crystal form control agent is prepared by compounding N-hydroxyethylethylenediaminetriacetic acid and ammonium sulfate in a mass ratio of 1:1, and the added amount is 0.8% of the dry basis mass of the lime slurry.

[0062] The stirring speed is 600 r / min.

[0063] The lime slurry dropping rate is 80 mL / min, and the sodium carbonate solution dropping time is consistent with the lime slurry dropping time.

[0064] The drying process temperature is 100° C., and the drying is done in an oven.

[0065] Example 2

[0066] A method for preparing stacked spherical calcium carbonate comprises the following steps:

[0067] S1: limestone is calcined at 1000°C for 300 min to prepare lime, the lime is digested, left to stand for 48 hours, and sieved to remove impurities to prepare lime slurry, and the solid content of the lime slurry is adjusted to 7% for standby use.

[0068] S2: Measure the amount of sodium carbonate according to the chemical reaction equation and prepare a sodium carbonate solution for use.

[0069] S3: Weigh 10 kg of tap water and pour it into the carbonization tower, control the initial water temperature to 35°C, add a crystal control agent, and start stirring.

[0070] S4: Use a peristaltic pump to simultaneously add lime slurry and sodium carbonate solution to the carbonization tower at a certain drop rate for reaction. After the drop addition is completed, continue stirring for 0.5h to allow sufficient reaction.

[0071] S5: Heat the reacted solution to 90°C and keep it for 1 hour.

[0072] S6: The suspension obtained in step S5 is filtered, dried and sieved to finally obtain stacked spherical calcium carbonate.

[0073] The sodium carbonate solution is prepared at a concentration of 0.1 mol / L.

[0074] The crystal form control agent is prepared by compounding N-hydroxyethylethylenediaminetriacetic acid and ammonium sulfate in a mass ratio of 1:1, and the added amount is 0.3% of the dry basis mass of the lime slurry.

[0075] The stirring speed is 600 r / min.

[0076] The lime slurry dropping rate is 50 mL / min, and the sodium carbonate solution dropping time is consistent with the lime slurry dropping time.

[0077] Example 3

[0078] A method for preparing stacked spherical calcium carbonate comprises the following steps:

[0079] S1: limestone is calcined at 1000°C for 300 min to prepare lime, the lime is digested, left to stand for 48 hours, and sieved to remove impurities to prepare lime slurry, and the solid content of the lime slurry is adjusted to 11% for standby use.

[0080] S2: Measure the amount of sodium carbonate according to the chemical reaction equation and prepare a sodium carbonate solution for use.

[0081] S3: Weigh 10 kg of tap water and pour it into the carbonization tower, control the initial water temperature to 50°C, add a crystal control agent, and start stirring.

[0082] S4: Use a peristaltic pump to simultaneously add lime slurry and sodium carbonate solution to the carbonization tower at a certain drop rate for reaction. After the drop addition is completed, continue stirring for 0.5h to allow sufficient reaction.

[0083] S5: The reacted solution was heated to 90°C and kept for 3 hours.

[0084] S6: The suspension obtained in step S5 is filtered, dried and sieved to finally obtain stacked spherical calcium carbonate.

[0085] The sodium carbonate solution is prepared at a concentration of 0.5 mol / L.

[0086] The crystal form control agent is prepared by compounding N-hydroxyethylethylenediaminetriacetic acid and ammonium sulfate in a mass ratio of 1:1, and the added amount is 1.5% of the dry basis mass of the lime slurry.

[0087] The stirring speed is 600 r / min.

[0088] The lime slurry dropping rate is 100 mL / min, and the sodium carbonate solution dropping time is consistent with the lime slurry dropping time.

[0089] Comparative Example 1

[0090] A method for preparing calcium carbonate comprises the following steps:

[0091] S1: limestone is calcined at 1000°C for 300 min to prepare lime, the lime is digested, left to stand for 48 hours, and sieved to remove impurities to prepare lime slurry, and the solid content of the lime slurry is adjusted to 9% for standby use.

[0092] S2: Measure the amount of sodium carbonate according to the chemical reaction equation and prepare a sodium carbonate solution for use.

[0093] S3: Weigh 10 kg of tap water and pour it into the carbonization tower, control the initial water temperature to 48°C, and start stirring.

[0094] S4: Use a peristaltic pump to simultaneously add lime slurry and sodium carbonate solution to the carbonization tower at a certain drop rate for reaction. After the drop addition is completed, continue stirring for 0.5h to allow sufficient reaction.

[0095] S5: The reacted solution was heated to 90°C and kept warm for 2 hours.

[0096] S6: The suspension obtained in step S5 is filtered, dried and sieved to finally obtain calcium carbonate.

[0097] The sodium carbonate solution is prepared at a concentration of 0.3 mol / L.

[0098] The stirring speed is 600 r / min.

[0099] The lime slurry dropping rate is 80 mL / min, and the sodium carbonate solution dropping time is consistent with the lime slurry dropping time.

[0100] The drying process temperature is 100° C., and the drying is done in an oven.

[0101] Comparative Example 2

[0102] A method for preparing calcium carbonate comprises the following steps:

[0103] S1: limestone is calcined at 1000°C for 300 min to prepare lime, the lime is digested, left to stand for 48 hours, and sieved to remove impurities to prepare lime slurry, and the solid content of the lime slurry is adjusted to 9% for standby use.

[0104] S2: Measure the amount of sodium carbonate according to the chemical reaction equation and prepare a sodium carbonate solution for use.

[0105] S3: Weigh 10 kg of tap water and pour it into the carbonization tower, control the initial water temperature to 65°C, add a crystal control agent, and start stirring.

[0106] S4: Use a peristaltic pump to simultaneously add lime slurry and sodium carbonate solution to the carbonization tower at a certain drop rate for reaction. After the drop addition is completed, continue stirring for 0.5h to allow sufficient reaction.

[0107] S5: The reacted solution was heated to 90°C and kept for 2 hours.

[0108] S6: The suspension obtained in step S5 is filtered, dried and sieved to finally obtain calcium carbonate.

[0109] The sodium carbonate solution is prepared at a concentration of 0.3 mol / L.

[0110] The crystal form control agent is prepared by compounding N-hydroxyethylethylenediaminetriacetic acid and ammonium sulfate in a mass ratio of 1:1, and the added amount is 0.8% of the dry basis mass of the lime slurry.

[0111] The stirring speed is 600 r / min.

[0112] The lime slurry dropping rate is 80 mL / min, and the sodium carbonate solution dropping time is consistent with the lime slurry dropping time.

[0113] The drying process temperature is 100° C., and the drying is done in an oven.

[0114] Comparative Example 3

[0115] A method for preparing calcium carbonate comprises the following steps:

[0116] S1: limestone is calcined at 1000°C for 300 min to prepare lime, the lime is digested, left to stand for 48 hours, and sieved to remove impurities to prepare lime slurry, and the solid content of the lime slurry is adjusted to 9% for standby use.

[0117] S2: Measure the amount of sodium carbonate according to the chemical reaction equation and prepare a sodium carbonate solution for use.

[0118] S3: Weigh 10 kg of tap water and pour it into the carbonization tower, control the initial water temperature to 48°C, add a crystal control agent, and start stirring.

[0119] S4: Use a peristaltic pump to simultaneously add lime slurry and sodium carbonate solution to the carbonization tower at a certain drop rate for reaction. After the drop addition is completed, continue stirring for 0.5h to allow sufficient reaction.

[0120] S5: The reacted solution was heated to 90°C and kept warm for 2 hours.

[0121] S6: The suspension obtained in step S5 is filtered, dried and sieved to finally obtain calcium carbonate.

[0122] The sodium carbonate solution is prepared at a concentration of 0.3 mol / L.

[0123] The crystal form control agent is prepared by compounding N-hydroxyethylethylenediaminetriacetic acid and ammonium sulfate in a mass ratio of 1:1, and the added amount is 0.8% of the dry basis mass of the lime slurry.

[0124] The stirring speed is 600 r / min.

[0125] The lime slurry dropping rate is 150 mL / min, and the sodium carbonate solution dropping time is consistent with the lime slurry dropping time.

[0126] The drying process temperature is 100° C., and the drying is done in an oven.

[0127] The calcium carbonate products prepared in Examples 1 to 3 of the present invention and Comparative Examples 1 to 3 were subjected to scanning electron microscopy, and the results showed that Figures 1 to 6 .

[0128] from Figures 1 to 6 In the detailed comparative analysis, we can clearly see the significant technical advantages and progress of the present invention in the regulation of calcium carbonate morphology and the construction of stacked structures. First, focusing on Examples 1, 2, and 3, these examples have successfully achieved the precise preparation of stacked spherical calcium carbonate. This achievement not only demonstrates a high degree of morphology control ability, but also reflects the exquisite regulation of the interaction force between calcium carbonate particles. The stacked spherical structure not only increases the specific surface area of ​​the material, provides more active sites for subsequent chemical reactions or physical adsorption, but also significantly improves the mechanical strength and stability of the material, broadening its application potential in multiple fields (such as drug carriers, catalyst carriers, coatings, and plastic fillers, etc.).

[0129] On the other hand, the significant defect of Comparative Example 1 is that no crystal form controller is added, resulting in the generated calcium carbonate particles showing a micron-sized block shape and lacking a stacking structure. This result directly compares the key role of the crystal form controller in regulating the morphology and stacking process of calcium carbonate. By accurately selecting and introducing a suitable crystal form controller, the present invention effectively guides the growth direction of calcium carbonate crystals, realizes the transformation from disorder to order, from a single form to a complex stacking structure, and reflects the great progress brought about by technological innovation.

[0130] Looking at Comparative Example 2, the initial water temperature is set too high, which directly affects the kinetics of crystal nucleation and growth, resulting in uneven distribution of the size of the generated calcium carbonate particles, and the stacking phenomenon becomes blurred and not obvious. This comparison not only reveals the sensitivity of the physical parameter of temperature in crystal engineering, but also emphasizes the fine adjustment ability of the present invention in temperature control, ensuring the stability of the crystal growth environment, thereby achieving a uniform and orderly stacking structure.

[0131] Finally, in Comparative Example 3, the drop acceleration rate of the calcium hydroxide suspension was too fast, resulting in different particle generation speeds, which in turn affected the uniformity and stacking effect of the particles. This phenomenon profoundly reflects the importance of process control to the final product morphology. In contrast, the present invention achieves fine control of the crystal growth process by optimizing process parameters such as drop acceleration rate and stirring intensity, ensuring that each calcium carbonate particle can grow under optimized conditions, and finally forming a compact and orderly stacking structure, reflecting a significant technological advancement in process control.

[0132] In summary, by comparing the embodiments and comparative examples, the present invention significantly improves the morphology control ability and stacking structure quality of calcium carbonate, not only enriches the types and properties of calcium carbonate materials, but also lays a solid foundation for its wide application. The successful implementation of this technology is not only a major innovation in the traditional calcium carbonate preparation process, but also an important breakthrough in the field of materials science.

Claims

1. A method for preparing stacked spherical calcium carbonate, characterized in that, The following steps are involved: S1: calcining limestone to prepare lime, and preparing lime slurry by digesting, standing, and sieving to remove impurities; S2: according to the chemical reaction equation, the amount of sodium carbonate is measured and the sodium carbonate solution is prepared for standby use; S3: Pour weighed water into the carbonization tower, control the initial water temperature, add a crystal form control agent, and start stirring; S4: using a peristaltic pump to simultaneously add lime slurry and sodium carbonate solution to the carbonization tower at a certain drop rate for reaction. After the dropwise addition is completed, continue stirring to fully react; S5: heating the reacted solution and performing heat preservation and aging; S6: The suspension obtained in step S5 is filtered, dried and sieved to finally obtain stacked spherical calcium carbonate.

2. The preparation method of stacked spherical calcium carbonate according to claim 1, characterized in that, In step S1, limestone is calcined at 1000° C. for 300 min to prepare lime; the standing time is 48 hours; and the solid content of the lime slurry is adjusted to 7-11% for standby use.

3. The preparation method of stacked spherical calcium carbonate according to claim 1, characterized in that, The sodium carbonate solution in step S2 is prepared at a concentration of 0.1 to 0.5 mol / L.

4. The preparation method of stacked spherical calcium carbonate according to claim 1, characterized in that, In step S3, 10 kg of tap water is weighed and poured into the carbonization tower, and the initial water temperature is controlled to be 35-50° C.; the crystal form control agent is compounded by N-hydroxyethylethylenediaminetriacetic acid and ammonium sulfate in a mass ratio of 1:1, and the added amount is 0.3-1.5% of the dry basis mass of the lime slurry.

5. The preparation method of stacked spherical calcium carbonate according to claim 1, characterized in that, The stirring speed in step S3 is 600 r / min.

6. The preparation method of stacked spherical calcium carbonate according to claim 1, characterized in that, The lime slurry dropping rate in step S4 is 50-100 mL / min, and the sodium carbonate solution dropping time is consistent with the lime slurry dropping time.

7. The preparation method of stacked spherical calcium carbonate according to claim 1, characterized in that, In step S4, stirring was continued for 0.5 h.

8. The preparation method of stacked spherical calcium carbonate according to claim 1, characterized in that, In step S5, the insulation temperature is 90° C. and the insulation is carried out for 1 to 3 hours.

9. The preparation method of stacked spherical calcium carbonate according to claim 1, characterized in that, The drying process temperature in step S6 is 100° C., and the product is dried in an oven.

10. A stacked spherical calcium carbonate prepared according to the method according to any one of claims 1 to 9.

Citation Information

Patent Citations

  • Preparation method of flake-stacked cube-shaped micron-sized calcium carbonate

    CN104445334A

  • A method for preparing a hemispherical calcium carbonate structure

    CN106118135B

  • Preparation method of calcium carbonate with layered structure

    CN108439447A

  • Rugby-shaped calcium carbonate and preparation process thereof

    CN109809458A

  • Preparation method of calcium carbonate with woven shape

    CN112591780A